Pseudosarcomatous Fibromyxoid Tumor of the Prostate - Gokhan Atis; Cenk Gurbuz; Murat Can Kiremit; Bayram Guner; Ebru Zemheri; Turhan Caskurlu (The Scientific World Journal)
We present the case of a 61-year-old patient who was evaluated for benign infravesical obstruction due to a pseudosarcomatous fibromyxoid tumor of the prostate. This entity is rare and difficult to distinguish from a malignant lesion. A discussion of the pathological features and a review of the literature are given.